PERANCANGAN ALAT PEMBERSIH AC UNIT IN DOOR DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Christian, Kevin; Sukania, I Wayan; Utama, Didi Widya (Universitas Tarumanagara, 2024)
As we know, every house nowadays definitely has at least one or two air conditioners, so this product definitely has to go through the maintenance stage so that the tools needed must also be adequate, but when we look again carefully at the tools that currently exist There are still some shortcomings, such as when someone wants to clean the AC, there is quite a bit of dew produced by the existing product that splatters, causing the floor to become wet and also the method of use is also quite simple but not optimal because most tools nowadays only use clear cloth and of course when the author wants to carry out an analysis of the product that will be designed, it is natural that it goes through several stages so that the product can sell and is in accordance with the wishes of the current community so that the stages for designing the product must go through various aspects such as using the method used by the author, namely the QFD method so that the product is can be produced according to the target desired by the author. For the product that will be designed, light materials will be used to avoid work accidents for both officers and the air conditioner itself and also to facilitate the mobility of the air conditioner so that the material chosen is polypropylene plastic pellets, where the plastic pellets will go through a molding process so that they will produce The product is in accordance with the author’s wishes, which has been confirmed to be of a reasonable size and the advantages of the product designed can be expected to make it easier for everyone to clean the AC, both in terms of installing the product and using the product.